2019
DOI: 10.4049/jimmunol.1900400
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 Binding Protein Promotes the Disease Process in Multiple Sclerosis

Abstract: Genome-wide association studies have mapped the specific sequence variants that predispose for multiple sclerosis (MS). The pathogenic mechanisms that underlie these associations could be leveraged to develop safer and more effective MS treatments but are still poorly understood. In this article, we study the genetic risk variant rs17066096 and the candidate gene that encodes IL-22 binding protein (IL-22BP), an antagonist molecule of the cytokine IL-22. We show that monocytes from carriers of the risk genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The severity of inflammation was positively correlated with the level of IL-22BP in the cerebrospinal fluid of patients with MS. IL-22BP has a pathogenic effect on EAE in both mice and rats, and IL-22BP is theoretically an antagonist of IL-22. IL-22BP has been proposed to reduce IFN-γ produced by brain-derived T cells in lymph nodes ( 92 ). Previous studies showed that the histopathological features of EAE in IL-22-deficient mice were comparable to those in wild-type mice ( 14 ).…”
Section: Th22 Cells In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of inflammation was positively correlated with the level of IL-22BP in the cerebrospinal fluid of patients with MS. IL-22BP has a pathogenic effect on EAE in both mice and rats, and IL-22BP is theoretically an antagonist of IL-22. IL-22BP has been proposed to reduce IFN-γ produced by brain-derived T cells in lymph nodes ( 92 ). Previous studies showed that the histopathological features of EAE in IL-22-deficient mice were comparable to those in wild-type mice ( 14 ).…”
Section: Th22 Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…Previous studies showed that the histopathological features of EAE in IL-22-deficient mice were comparable to those in wild-type mice ( 14 ). Hannes et al conducted EAE experiments on wild-type mice, IL-22 deficient mice, IL-22BP deficient mice, and IL-22 and IL-22BP double deficient mice and concluded that the loss of control of IL-22 signal in IL-22BP deficient mice reduced the severity of EAE,which supported the protective effect of IL-22 in MS; thus, they suggested that IL-22BP could be used as a new target for MS ( 92 ).…”
Section: Th22 Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…On the contrary, TGF-β ( 53 ), ICOS ( 54 ), and IL-27 ( 55 ) have also been shown to prevent the production of IL-22. Lastly, IL-22BP is a natural inhibitor of IL-22, having more than a 20-fold higher affinity for IL-22 than the cell surface receptor chain IL-22R1 ( 56 ), thus playing a pathogenic role in inflammatory bowel disease (IBD) ( 57 ) and multiple sclerosis ( 58 ) patients.…”
Section: Regulation Of Il-10 and Il-22 Secretion By Mucosal Immune Cementioning
confidence: 99%
“…In a follow-up study the role of IL-22BP in EAE was further dissected using an inducible in vivo IL-22BP knockdown rat strain. Reducing IL-22BP expression before EAE immunization results in reduced incidence and severity of disease in conjunction with increased proportions of Tregs and decreased proportions of Th1 cells in the lymph nodes that drain the site of immunization ( 80 ). Taken together, IL-22 appears to have a protective effect in autoimmune neuroinflammation but, unlike many other animal models discussed in this article, the effect of endogenous IL-22 is normally blocked by IL-22BP.…”
Section: The Influence Of Interleukin-22 On the Th1/th17 Axismentioning
confidence: 99%